Economic Cost of Childhood Unintentional Injuries - Lao, Zhiqin (Medknow Publications & Media Pvt Ltd, 2012)
AIMS: This study aims to review the economic cost of childhood (0-18 years) unintentional injuries (UI) and focuses upon comparing the cost burden between developing and developed countries. METHODS: Articles were selected from PUBMED using the search words “Economic Cost”, “Unintentional injuries” and “Children”. Nine articles were selected. RESULTS: Studies in China focused upon cost to hospitals, in Bangladesh they focused on personal payment in rural areas, and in Vietnam they focused upon community-based cost analysis. There was one study from Norway on UI at home. There were 5 articles from the USA focusing on submersion injury, UI insurance, unintentional traumatic brain injury, UI due to firearms and UI medical costs. The cost of childhood UI is enormous, ranging from US $516,938 to US $9,550,704 per year. This represents a large economic burden on society. Additionally, there is a large gap between lower-middle income countries (LMIC) and high income countries (HIC) in the burden of injury, injury health care and insurance systems. CONCLUSION: Different bases and contexts of studies make it difficult to draw a solid conclusion about the amount of costs of UI among children. Therefore, more studies of children's unintentional injuries should be carried out in low and middle income countries.